O Programa Ensino Integral e a Nova Gestão Pública: intensificação dos mecanismos de gestão e regulação de escolas estaduais paulistas - Silva, Abel José da (Universidade Federal de São Carlos, 2021)
This work is affiliated with the State, Politics and Human Formation research line of the Post- Graduate Program in Education at the Federal University of São Carlos, aligned with the research and theorizing objectives that involve, among others, public policies and school institutions and the realization and belonging contradictions. In this sense, this work has as its object of study the intensification of the management and regulation mechanisms of the Integral Education Program (PEI). Strategy to expand school hours contained in the Integral Education pillar of the São Paulo Education-Commitment Program (PECSP). This program has centralized several educational policies aimed at the state public education system in São Paulo since the publication of Decree No. 57.571/2011. The Integral Education Program (PEI) was instituted by the state government of São Paulo since 2012, through LC's nº 1.164/2012, Law nº 1.191/2012 and regulated by Decree nº 59.354/2013, with the purpose of increasing results in the indices and qualitative indicators of student learning in their schools. To this end, the Program focuses on changes that encompass school management, curriculum and teaching work, bringing together in this process managerial mechanisms from the private business sphere to the school units of the state teaching network of PEI. Based on this context, it was defined as the objective of this work to identify and analyze the intensification of the management and regulation mechanisms arising from the New Public Management inserted in the schools of the Integral Education Program, from the study of its political-ideological foundations and its structure and functioning. This study is based on bibliographic and documentary analysis of the Program, focusing on the management and regulation mechanisms of the São Paulo state school inserted by the state with the PEI, based on the following categories of analysis: Subjects and their roles in the PEI; Contracting process; Control, evaluation and professional performance mechanisms in PEI. It was observed from the work that the PEI uses as foundation the managerial model of management disciplined by the NGP and the economistic logic for its educational offer, under the determinations arising from the general guidelines of the reorganization of the public school system in São Paulo as administrative rationalization ( autonomy and computerization, for example), financial (deconcentration, decentralization of resources and competences, for example) and pedagogical (school flow and single curriculum, for example), present in this cycle of psdbist administrations in the government of the state of São Paulo.
The Integral Education Program and the New Public Management: intensification of the mechanisms of management and regulation of state schools in São Paulo
Keywords: Programa Ensino Integral; Política Educacional Paulista; Nova Gestão Pública; Integral Education Program; Paulista Educational Policy; New Public Management; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO